LVDC Bipolar Balance Control of I-M2C in Urban AC/DC Hybrid Distribution System - Li, Liangzi; Sun, Kaiqi; Liu, Zhijie; Wang, Wenning; Li, Ke-Jun (Frontiers in Energy Research, 2022)
With the high proportional renewable energy integration and rapid increase of the DC loads such as the electric vehicle and distributed energy storage, the DC distribution system becomes a prospective solution to urban power grid enhancement for its high-efficiency and eco-friendly. In most DC distribution systems, power interfaces are applied to connect low voltage DC (LVDC) distribution systems with multiple medium voltage (MV) systems in order to improve the operating reliability and economy. Compared to other types of multi-ports power interfaces, three-ports isolated modular multilevel converter (I-M2C) has shown many advantages, including low cost, high power density, and low control complexity. However, I-M2C cannot handle the power imbalance at the bipolar LVDC port like the other MMC-based three-ports power interfaces, which limits the operating range and decreases the stability of I-M2C in bipolar LVDC application. In order to solve the bipolar imbalance problems, a novel balance control method is proposed in this paper. The proposed balance control method is based on symmetrical decomposition. By decoupling the MV power control and the LV bipolar power compensation control, the proposed method can eliminate the bipolar voltage deviation in different working conditions. The simulation results prove the validity and good control performance of the proposed method.